Polymorphisms of NFκB1 and IκBα and Their Synergistic Effect on Nasopharyngeal Carcinoma Susceptibility. (16th June 2015) - Liu, Yehua; Qiu, Fuman; Yang, Lei; Yang, Rongrong; Yang, Xiaorong; Huang, Dongsheng; Fang, Wenxiang; Zhang, Lisha; Jiang, Qingping; Zhang, Lan; Zhou, Yifeng; Lu, Jiachun
Abstract : Nasopharyngeal carcinoma (NPC) is a multifactoral and polygenic disease with high prevalence in Southeast Asia and Southern China. Environmental factors and genetic susceptibility play important roles in NPC pathogenesis. In the present study, we tested the hypothesis that single nucleotide polymorphisms (SNPs) in nuclear factor-kappa B ( NF κ B ) and its inhibitor ( I κ B α ) conferred consistent risks for NPC. Four putatively functional SNPs ( NF κ B1 : rs28362491del>ins ATTG; NF κ B2 : rs12769316G>A; I κ B α : rs2233406C>T and rs696G>A) were analyzed to evaluate their associations with NPC risk in total 1590 NPC cases and 1979 cancer-free controls. We found that the rs28362491 insATTG variants (ins/del + ins/ins) in NF κ B1 conferred an increased risk of NPC (odds ratio [ OR ] = 1.30, 95% confidence interval [ CI ] = 1.09 –1.55, and P = 2.80 × 10 - 3 ) compared with the del/del homozygous genotype. The rs696AA variant in I κ B α had an increased risk of NPC (OR = 1 . 41, 95% CI = 1.20 –1.66, and P = 2.28 × 10 - 5 ) by decreasing I κ B α expression due to the modulation of microRNA hsa-miR-449a. Furthermore, both adverse genotypes of NF κ B/I κ B α and their interaction also exerted an increased risk on NPC. Taken together, Our findings indicated that genetic variants in NF κ B1 (rs28362491del>ins ATTG) and I κ B α (rs696G>A) and their synergistic effect might contribute to NPC predisposition.